2017
DOI: 10.1212/wnl.0000000000004515
|View full text |Cite
|
Sign up to set email alerts
|

Randomized open-label trial of dextromethorphan in Rett syndrome

Abstract: This study provides Class IV evidence that dextromethorphan at various doses does not change EEG spike counts over 6 months, though precision was limited to exclude an important effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 19 publications
(18 reference statements)
0
16
0
2
Order By: Relevance
“… • Effect sizes (with CI): ➢ CGI-I: − 0.554 (− 1.34, 0.23) ➢ Caregiver Top 3 Concerns: − 0.63 (− 1.42, 0.16) ➢ MBA change index: − 0.607 (− 1.39, 0.18) [ 131 ] Smith-Hicks et al (2017) 38 e 6 Randomised open-label Dextromethorphan EEG • Cognitive status: ➢ MSEL ➢ VABS • Behavioural characterisation: ➢ Parent-completed ABC–Community Version ➢ *SSI ➢ RSSS • Gait • EEG Dose dependent improvements deemed to be of statistical significance were noted for clinical seizures, receptive language and behavioural hyperactivity; however, there was no statistically significant improvement in global severity as assessed by the RSSS. [ 130 ] Yuge et al 2017 4 10-24 f Pilot open-label Ghrelin Not measured • SDCF to assess clinical and neurological parameters • BFMDRS score to assess dystonia • VAS Following treatment, improvement in scores were noted for: • SDCF for Patient 1 (31 [baseline] to 29 [2 years]) and Patient 2 (20 [baseline] to 18 [10 months]) • BFMDRS for Patient 1 (108.5 [baseline] to 100 [2 years]) and Patient 2 (67 [baseline] to 54.5 [10 months]) • Change in baseline in VAS for dystonia, tremor and sympathetic vasomotor reflexes in patient 1 and 2. [ 129 ] Nissenkorn et al 2017 14 6 (planned) Open-label (Phase 2) Glatiramer Acetate Noninvasive respiratory inductance plethysmography Primary: • Safety, tolerability of treatment • Decrease in epileptiform activity Secondary: • Seizure frequency • Improvement in respiratory dysfunction • Improvement in core features assessed by Kerr and Naidu validated severity scores) Study was terminated due to treatment related serious adverse events in four patients.…”
Section: Ebad As a Target For Clinical Trials In Rttmentioning
confidence: 99%
See 2 more Smart Citations
“… • Effect sizes (with CI): ➢ CGI-I: − 0.554 (− 1.34, 0.23) ➢ Caregiver Top 3 Concerns: − 0.63 (− 1.42, 0.16) ➢ MBA change index: − 0.607 (− 1.39, 0.18) [ 131 ] Smith-Hicks et al (2017) 38 e 6 Randomised open-label Dextromethorphan EEG • Cognitive status: ➢ MSEL ➢ VABS • Behavioural characterisation: ➢ Parent-completed ABC–Community Version ➢ *SSI ➢ RSSS • Gait • EEG Dose dependent improvements deemed to be of statistical significance were noted for clinical seizures, receptive language and behavioural hyperactivity; however, there was no statistically significant improvement in global severity as assessed by the RSSS. [ 130 ] Yuge et al 2017 4 10-24 f Pilot open-label Ghrelin Not measured • SDCF to assess clinical and neurological parameters • BFMDRS score to assess dystonia • VAS Following treatment, improvement in scores were noted for: • SDCF for Patient 1 (31 [baseline] to 29 [2 years]) and Patient 2 (20 [baseline] to 18 [10 months]) • BFMDRS for Patient 1 (108.5 [baseline] to 100 [2 years]) and Patient 2 (67 [baseline] to 54.5 [10 months]) • Change in baseline in VAS for dystonia, tremor and sympathetic vasomotor reflexes in patient 1 and 2. [ 129 ] Nissenkorn et al 2017 14 6 (planned) Open-label (Phase 2) Glatiramer Acetate Noninvasive respiratory inductance plethysmography Primary: • Safety, tolerability of treatment • Decrease in epileptiform activity Secondary: • Seizure frequency • Improvement in respiratory dysfunction • Improvement in core features assessed by Kerr and Naidu validated severity scores) Study was terminated due to treatment related serious adverse events in four patients.…”
Section: Ebad As a Target For Clinical Trials In Rttmentioning
confidence: 99%
“…Using a variety of outcome measures, improvements were noted in the core clinical features following dextromethorphan [ 130 ] and high dose trofinetide (IGF-1 tripeptide analogue) [ 131 ] treatment in RTT patients. Interestingly, in these studies not all parameters that were evaluated demonstrated improvements.…”
Section: Ebad As a Target For Clinical Trials In Rttmentioning
confidence: 99%
See 1 more Smart Citation
“…Rett syndrome (RTT) is a neurological disorder associated with variants in the methyl-CpG binding protein 2 ( MECP2 ) gene. Recent research in RTT has progressed rapidly,1–6 with increasing classification of MECP2 genotype-Rett phenotype relationships,7–10 advances in understanding cognitive processing,11 and hints at possible therapies 1–5 12–15. A key feature of RTT is the dysregulation of autonomic circuits that may contribute to sudden death 16–22.…”
Section: Introductionmentioning
confidence: 99%
“…A disruption in the balance between excitation and inhibition and between GABA and glutamate pathways is implicated in RTT 80 . Dextromethorphan, an NMDA receptor antagonist, has been tested for its capacity to restore normal EEG function and reduce seizure, and although no significant improvement in global severity was noticed, statistically significant changes were seen in clinical seizures, language, and behavioral hyperactivity 81 .…”
Section: Clinical Trialsmentioning
confidence: 99%